Job Motivation, Job Satisfaction and Role Performance of Tabika Perpaduan Teachers in Peninsular Malaysia - Abdul Rauf, Habsah (1986)
The primary purpose of this study was to identify the intrinsic and the extrinsic factors of motivation perceived important by the TABIKA teachers and their relationships with job satisfaction. It was also to determine the extent to which the TABIKA teachers perform their job and the relationships between job satisfaction and their role performance. Data for this study were gathered from 110 TABIKA teachers of the National Unity Department through group self-administered questionnaires. The study revealed that all the intrinsic and extrinsic factors of motivation were perceived important by the TABIKA teachers. Ranking of intrinsic motivation categories in descending order of importance were self-achievement, self actualization, social, autonomy and job security categories.